Developing Effective Strategies to Enhance Customer Satisfaction: A Case Study of Absolut Chocolat, a Dessert-preneur in Malaysia - Mohamad Shukri, Nor Hazirah; Hasnul Hadi, Maisara; Supari, Nurul Wahidatul Syazwa; Mohd Ishar, Nor Irvoni (Creative Business and Sustainability Journal, 2023)
The attainment of customer satisfaction holds significant importance for the achievement of business success. Especially for nascent small and medium enterprises (SMEs) functioning within the fiercely competitive food industry, this initial step is a crucial milestone in achieving enduring viability and eventual success. Absolut Chocolat (AC) is a Malaysian startup dessert brand that entered the dessert industry in 2018. Since its inception, it has been able to attract adherents with its distinctive identity. However, as of late, the brand has had challenges upholding consumer satisfaction. The present study seeks to investigate the satisfaction of AC customers and the various elements that have an impact on it, including product quality, pricing, place, and service quality. The study utilizes an applied research methodology and a three-step inquiry process with diverse approaches, including SWOT analysis, regression analysis, and the TOWS Matrix. Using purposive sampling, data from 117 customers of AC was obtained via a survey questionnaire. Out of the four factors investigated, only price and product quality were found to have a positive effect on customer satisfaction. These findings have led to the formulation of several recommendations aimed at enhancing customer satisfaction among AC customers. Finally, this study not only adds to the body of knowledge on consumer satisfaction in the food segment for SMEs, but it also provides practical insights that can support the growth of companies like Absolut Chocolat and other comparable establishments.